2008
DOI: 10.1074/jbc.m705630200
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction between Nitrite and Oxyhemoglobin

Abstract: The nitrite anion (NO 2 ؊ ) has recently received much attention as an endogenous nitric oxide source that has the potential to be supplemented for therapeutic benefit. One major mechanism of nitrite reduction is the direct reaction between this anion and the ferrous heme group of deoxygenated hemoglobin. However, the reaction of nitrite with oxyhemoglobin (oxyHb) is well established and generates nitrate and methemoglobin (metHb). Several mechanisms have been proposed that involve the intermediacy of protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 36 publications
(32 reference statements)
7
103
2
Order By: Relevance
“…The electronic absorption spectra of the samples were measured with a grating spectrophotometric microplate reader (SH-1200; Corona Corporation, Sanjo, Japan). Previous studies demonstrated that a peak at 620 nm in the spectrum indicates specific absorption of metHb, whereas fairly sharp peaks located at 545 and 580 nm represent the absorption spectrum of a mixture of oxyHb and metHb (14)(15)(16)(17).…”
Section: Cyst Fluid Hemoglobin Species In Endometriosis and Its Maligmentioning
confidence: 99%
“…The electronic absorption spectra of the samples were measured with a grating spectrophotometric microplate reader (SH-1200; Corona Corporation, Sanjo, Japan). Previous studies demonstrated that a peak at 620 nm in the spectrum indicates specific absorption of metHb, whereas fairly sharp peaks located at 545 and 580 nm represent the absorption spectrum of a mixture of oxyHb and metHb (14)(15)(16)(17).…”
Section: Cyst Fluid Hemoglobin Species In Endometriosis and Its Maligmentioning
confidence: 99%
“…NO 2 is also produced via the complex reaction of nitrite with oxyHb in a reaction that involves ferryl formation (77,91,135). Thus, low nitrite levels limit both the ferryl deactivation reaction and the oxyHb reactions.…”
Section: The Interplay Of Reduced Nox Generation and Enhanced Ferryl mentioning
confidence: 99%
“…Under these conditions, the resulting NO is likely to be captured by vacant deoxyheme sites to produce nitrosylated hemes (e.g., HbNO), which are very stable. When the blood becomes fully oxygenated, the reaction between nitrite and oxyHb becomes a source of the NO 2 c radical (91,135). Additionally, NO 2 c can also be generated through the reaction of ferryl Hb with nitrite (81) ( Table 3, Reaction 7).…”
Section: Preserving Transporting and Delivering Hb-derived Nox Bioamentioning
confidence: 99%
“…Instead, oxidation of the Hb takes place (23). We, therefore, compared the levels of metHb in the hemolysate before and after centrifugation, as well as the metHb levels in the dispersed pellet.…”
Section: Rbc-nomentioning
confidence: 99%